2014
DOI: 10.1155/2014/671963
|View full text |Cite
|
Sign up to set email alerts
|

Operational Efficiency of an Immunization Clinic Attached to Rural Health Training Centre in Delhi, India: A Time and Motion Study

Abstract: Background. Obtaining baseline data about current patterns of work is important for assessing the effects of interventions designed to improve care delivery. Time and motion studies allow for the most accurate measurement of structured components. Therefore, the present study was conducted to study the operational efficiency of an immunization clinic in Delhi, India. Methods. An observational cross-sectional study was conducted at the immunization clinic of Rural Health Training Centre in Delhi, India, from Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
6
1
Order By: Relevance
“…Similarly, a time-motion study done at the immunization clinic attached to a rural health center in Delhi found that 64.1% of their study participants spent their time waiting. 17 However, they attributed the reason for the long waiting time to the lack of health care workers, whereas in the present study, it was due to the non-adherence of the beneficiaries to the allotted time.…”
Section: Discussioncontrasting
confidence: 72%
“…Similarly, a time-motion study done at the immunization clinic attached to a rural health center in Delhi found that 64.1% of their study participants spent their time waiting. 17 However, they attributed the reason for the long waiting time to the lack of health care workers, whereas in the present study, it was due to the non-adherence of the beneficiaries to the allotted time.…”
Section: Discussioncontrasting
confidence: 72%
“…13 Many studies stated that in India major obstacles in achieving full immunization coverage are long waiting times and insufficient and inefficient staff. 14,15 Such problems are more severe in rural areas because of a lack of resources and infrastructure and especially if we are dealing with paediatric patients. 14,15 In the present study, it was observed that study participants must spend 20% of the total time spent in initial registration only.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Such problems are more severe in rural areas because of a lack of resources and infrastructure and especially if we are dealing with paediatric patients. 14,15 In the present study, it was observed that study participants must spend 20% of the total time spent in initial registration only. Though adequate healthcare workers are posted in immunization clinics long waiting times could be due to a lack of adequate healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…The average waiting time was found to be 44.85 minutes (17.92 minutes to 126.56 minutes in surgery and nephrology department respectively), average consultation time for all OPD was found to be 17.357 minutes (6.00 minutes in medicine department to 76.840 minutes in psychiatry department) (20). In another study ~ 70% of the population is served by facilities within a 2-hour transfer time to a hospital and spent 64.1% of their total time in waiting at the immunization clinics (21,22). Despite the challenges in accessibility of maternal and child health service for mothers and children in Ethiopia there is paucity of information about the average time spent and its determinants in using the service; hence the current study aims to ll this gap.…”
Section: Introductionmentioning
confidence: 99%